Intermediasi Sosial Bank Sumut Syariah KCP Perdagangan terhadap Pemberdayaan UMKM Syariah - Nurul Ni'mah Qodriyah; Tuti Anggraini; Juliana Nasution (Jurnal Akuntansi dan Keuangan Islam, 2025)
The long-term role of Islamic banking as a social intermediation institution is often criticized for failing to reflect the true essence of Islamic financial principles. As a result, Islamic banks are frequently perceived as not significantly different from conventional banks, particularly in addressing the fundamental socio-economic issues of society. This study aims to analyze the implementation of social intermediation based on sharia principles at Bank Sumut Syariah KCP Perdagangan and examine its contribution to the empowerment of micro-enterprises. This research employs a descriptive qualitative approach, with primary data collected through in-depth interviews. The findings indicate that Bank Sumut Syariah has carried out its social intermediation role effectively through financing schemes such as murabahah and musharakah, as well as savings products including general muamalat savings, student savings, Hajj savings, and deposits. The micro-financing procedures involve several stages from application to monitoring. This study fills a gap in the literature by examining local Islamic banking practices and provides insights into accountability and contributions to microeconomic empowerment.Peran jangka panjang perbankan syariah sebagai lembaga intermediasi sosial kerap dikritik karena dinilai belum mencerminkan esensi sejati dari sistem keuangan Islam. Akibatnya, perbankan syariah sering dianggap tidak berbeda secara signifikan dari perbankan konvensional, terutama dalam menjawab persoalan fundamental masyarakat. Bertujuan untuk menganalisis implementasi intermediasi sosial berbasis syariah pada Bank Sumut Syariah KCP Perdagangan serta mengkaji kontribusinya terhadap pemberdayaan usaha mikro, penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data primer melalui wawancara mendalam. Hasil penelitian menunjukkan bahwa Bank Sumut Syariah telah menjalankan fungsi intermediasi sosial dengan cukup baik melalui pembiayaan berbasis akad murabahah dan musyarakah, serta produk simpanan seperti tabungan muamalat dan tabungan haji. Prosedur pembiayaan mikro melibatkan tahapan mulai dari pengajuan hingga monitoring. Temuan ini mengisi kekosongan literatur mengenai praktik intermediasi sosial di unit perbankan syariah daerah dan memberikan wawasan mengenai akuntabilitas serta kontribusi nyata terhadap penguatan ekonomi masyarakat kecil.